Role of Diagnostic Laparoscopy in Identifying the cause of Chronic Abdominal Pain - Shahid Hussain Mirani, Dharmoon Arija, Muhammad Naeem, Abdul Rasheed Zai, Muhammad Rafique Pathan, Muhammad Anwar Memon (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Chronic abdominal pain is a prevalent and challenging medical condition characterized by persistent pain in the abdomen lasting for more than three months. The pain can be due to a variety of gastrointestinal and extra-gastrointestinal causes, and it often requires a multidisciplinary approach for diagnosis and management. Common causes include irritable bowel syndrome, inflammatory bowel disease, chronic pancreatitis, and adhesions, among others. Objective: To determine the role of diagnostic laparoscopy in identifying the cause of chronic abdominal pain. Methodology: This observational study was conducted at Department of Surgery, Ghulam Muhammad Mahar Medical College Sukkur in tertiary-care hospital from 1st January 2022 to 31st December 2023. A total of 80 patients having age of ≥20years were included. Patients who were suffering from abdominal pain for more than 6 months and having non-conclusive diagnosis were included. Results: Males were comparatively more in number as compared to females. Appendicitis was the main examination outcomes after laparoscopic evaluation followed by bands of adhesion. In 88% of the patients, total relief in pain was observed. Conclusion: Laparoscopy proves a definitive diagnosis in chronic abdominal pain’ patients and thus helps in therapeutic intervention. Keywords: Abdominal pain, Laparoscopy, Irritable bowel syndrome, Inflammatory bowel disease, Diagnostic method.